Enhanced Durability and Environmental Sustainability in Marine Infrastructure: Innovations in Anti-Corrosive Coating Technologies - Saavedra-Flores, E; Avudaiappan-, S (Elsevier B.V., 2025)
The sustained exposure of marine infrastructure to corrosive environments necessitates the adoption of advanced protective strategies. This review critically examines recent innovations in anti-corrosive coating technologies, with a focus on enhancing durability and promoting environmental sustainability in marine applications. By synthesizing cutting-edge developments in nanocomposite coatings, bio-based polymers, and smart functional materials, the paper offers a detailed evaluation of their protective mechanisms, application methods, and long-term performance under severe maritime conditions. Special attention is given to emerging deposition techniques and their influence on coating adhesion, uniformity, and resistance to mechanical and chemical degradation. The review further explores the integration of sustainability metrics, including lifecycle assessments, toxicity profiles, and regulatory compliance frameworks such as IMO and REACH. Through comparative analysis of recent studies, this work identifies critical performance benchmarks and existing knowledge gaps, thereby guiding future research directions. Ultimately, this paper presents a comprehensive and structured synthesis that informs the design and selection of eco-friendly, high-performance coatings crucial for extending the lifespan of marine infrastructure. © 2025